Graft copolymerization of 2-ethoxyethyl methacrylate onto liquid natural rubber using metal ion redox systems - Narumol Sirisongthum (Chulalongkorn University, 2013)
Thesis (M.Sc.) -- Chulalongkorn University, 1991